Video drain. (New Humanist)
The article focuses on the launch of a video game highlighting prevention in the spread of Christianity and Islam by an anonymous young programmer from Virginia. The video game has its ultimate aim to behead the prophet Muhammad. Furthermore, it reveals that establishment of the video game has manifested mischievousness of atheists to restrict outspreading of Christianity and Islam.